Survei Keterampilan Dasar Permainan Futsal Siswa Ekstrakulikuler di SMP Negeri 4 Ungaran Kabupaten Semarang - Utomo, Hidayah Mulyono; Setiawan, Fredy Eko; A, Aristiyanto; Amin, Nur; Herdinata, Guntur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted to determine the skill level of Passing, Knowing the skill level Controlling, Knowing the skill level Dribbling, Knowing the skill level Shooting. This research is a quantitative descriptive research with one variable without making comparisons or connecting with other variables. The tests designed to measure the basic skills of playing futsal include passing with controlling, dribbling and shooting. The results of this study are: the level of basic technical skills for playing futsal for extracurricular futsal participants at SMP Negeri 4 Ungaan is good considering the highest frequency in the good category with 7 students or 35% level of basic skills in playing futsal for extracurricular participants at SMP Negeri 4 Ungaran Barat in very good category 2 people or 10%, good 7 people or 35%, 4 people or 20% enough, 4 people less or 20%, very less 3 people or 15%. Conclusion : Based on the results of the research and discussion that have been presented, it can be concluded that the level of basic technical skills in playing futsal for futsal extracurricular participants at SMP Negeri 4 Ungaran is good considering the highest frequency in the good category with 7 students or 35%.